3-Adic System and Chaos. (30th November 2011) - Wang, Lidong; Li, Yingnan; Liao, Li
Abstract : Let( Z ( 3 ), τ ) be a 3-adic system. we prove in( Z ( 3 ), τ ) the existence of uncountable distributional chaotic set ofA ( τ ), which is an almost periodic points set, and further come to a conclusion thatτ is chaotic in the sense of Devaney and Wiggins.